MENINGKATKAN PERTUMBUHAN DAN HASIL PAKCOY (BRASSICA JUNCEARAPAL.) DENGAN MENGATUR DOSIS NUTRISI AB MIX AGRIFARM DAN UMUR BIBIT SECARA HIDROPONIK SISTEM NFT - I WAYAN SUKASANA; I NENGAH KARNATA; BUDI IRAWAN (Universitas Mahasaraswati Mataram, 2019)
Pakcoy is a type of mustard plant that is quite popular with the community, it is very suitable to be cultivated considering the need for vegetables is quite large. The community's need for fresh and pesticide-free vegetables is a choice now in line with the community's understanding of a healthy diet. Alternatives to fulfillment are chosen by planting with hydroponic media. Hydroponics is a substitute for soil media that can be used to grow vegetable crops. The presence of hydroponics is expected to be able to overcome the narrowing of agricultural land and reduce the use of pesticides considering that pesticides greatly affect human health and the environment. This study aims to determine the effect of nutritional doses of AB mix agrifarm and age of seedlings and their interactions on the growth and yield of pakcoy plants, this study is carried out in the experimental garden of the Faculty of Agriculture, Tabanan University which began on 9 December 2018 until 12 January 2019. The study used a Randomized Block Design (RBD) consisting of two factors. The first factor is the nutritional dose of AB mix agrifarm (N) which consists of three dose levels, namely the dose of 850 ppm, 1050 ppm and 1250 ppm. The second factor is the age of seedlings (U) which consists of two seedling age levels, namely the age of seedlings 1 week and 2 weeks. Each treatment is repeated four times. The results of the study obtained the interaction of dose agrifarm treatment with seed age showed a very significant effect (p 1 0.01) on all parameters except for the parameters of the number of leaves aged 35 days old which showed no significant effect (p 5 0.05). The economical wet weight of plant-1 and BKO of the highest yield of 1-crop yield is produced in the combination treatment of N3U, which amounted to respectively 244.09 g and 78.10g or increased respectively by 57.78% and 293.85% compared to results the lowest produced by the combination treatment of N1U1 is 154.71g and 19.83g